DIALECTICS AND THE EVOLUTION OF THOUGHT IN HISTORY: A PHILOSOPHICAL PERSPECTIVE OF HEGEL - Pratama, Putra (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
This article explores the concepts of history and dialectics in the perspective of Hegel's philosophy. History, defined as a science that studies concrete events based on the processes that occur, is understood through two key elements: events and dialectics. Events are absolute and objective, while dialectics is a communication process involving thesis, antithesis and synthesis. In Hegel's view, history not only records what happened but also describes the evolution of human thought through a dialectical process. According to Hegel: genuine history, reflective history, and philosophical history. Genuine history, as practiced by Herodotus and Thucydides, includes direct narration of events. Reflective history, outlined in Hegel's works such as the "Phenomenology of Spirit", describes the journey of human thought through time. Philosophical history, on the other hand, emphasizes the development of philosophy as a reflection of the history of human consciousness.